Weighted Moving Averages for a Series of Fuzzy Numbers Based on Nonadditive Measures with σ − λ Rules and Choquet Integral of Fuzzy-Number-Valued Function. (30th March 2020) - Gong, Zengtai; Lei, Wenjing; Liu, Kun; Qin, Na
Abstract : The aim of this study is to generalize moving average by means of Choquet integral. First, by employing nonadditive measures with δ  −  λ rules, the calculation of the moving average for a series of fuzzy numbers can be transformed into Choquet integration of fuzzy-number-valued function under discrete case. Meanwhile, the Choquet integral of fuzzy number and Choquet integral of fuzzy number vector are defined. Finally, some properties are investigated by means of convolution formula of Choquet integral. It shows that the results obtained in this paper extend the previous conclusions.